Sustitution of Megathyrsus maximus grass by square guineo and urea in silage mixtures - López-Herrera, Michael Jesús (2019)
Introduction. Tropical pastures have higher fiber content in proportion to other nutrients, this limits the dry matter intake by ruminants. Usage of additives in silage can improve nutritive content in forages that can be preserved to use in moments of lower forage availability. Objective. The objective of this research was to evaluate the effect of substituting Megathyrsus maximus cv Mombaza grass for immature square bananas (Musa ABB) and urea in silages. Materials and methods. The experiment was carried out between August and December 2016. A factorial design with eight treatments was used. The forage mixtures were stored for sixty days in bags of 5.0 kg bags. Results. Usage of square banana fruit produced an increase in pH, ammonia nitrogen, and urea. The fruit also increased the concentration of dry matter and non-fibrous carbohydrates, this improved the relative value of the forage and the energy content. On the other hand, urea improved the crude protein content by 10 percentage units, due to its contribution as non-proteic nitrogen. The energy content of the treatments fluctuated between 59.5 and 63.6% TND, in the treatments with greater use of square banana fruit. Conclusion. Silage with 30% of substitution by square banana fruit and 0.5 - 1.0% urea are considered an alternative for feeding ruminants, as a complement to a balanced diet.